Analysis of Variables for the Suitable Growth of a Latin American City in a Contemporary Context - Barrera, Oscar Saul Hernandez; Arango, Oscar Montano; Armenta, Jose Ramon Corona; Gomez, Humberto Ivan Navarro; Quiroz, Israel Aaron Palma; Marin, Joselito Medina (European Scientific Journal, ESJ, 2016)
Occupation in a city involves the process of continuous expansion. The fitness of a territory can be measured as a result of its physical, socioeconomic, and cultural variables. Hence, this is what lays the foundations for a comprehensive growth of human settlements. Also, it provides a setting that allows the social reproduction of its inhabitants beyond their basic needs. The way to predict its expression in the territory results to elements conceived through planning. This planning is conditional on the existing legal framework, and it is expressed during zoning which is exceeded in many cases. This research analyses the characteristics and practices of the planning process which is derived from various considerations in the international arena. It was conducted from a prospective approach to manage the territory with the aim of identifying variables that allows one to understand the dynamics of the physical expansion and growth of the cities. Also, it also opines success stories in order to define the basic components which are articulated in a harmonious and sustainable way.